Downward nominal rigidities and bond premia - François Gourio; Phuong Ngo (Federal Reserve Bank of Chicago, 2024)
We develop a parsimonious New Keynesian macro-finance model with downward nominal rigidities to understand secular and cyclical movements in Treasury bond premia. Downward nominal rigidities create state-dependence in output and inflation dynamics: a higher level of inflation makes prices more flexible, leading output and inflation to be more volatile, and bonds to become more risky. The model matches well the relation between the level of inflation and a number of salient macro-finance moments. Moreover, we show that empirically, inflation and output respond more strongly to productivity shocks when inflation is high, as predicted by the model.
Keywords: E31; E32; E43; E44; G12; 330; Term Premium; Bond premium; Phillips curve; Inflation; Asymmetry; Skewness